Building safer secondary schools in Uganda through collective commitment to health and safety compliance - Sekiwu, Denis; Kabanda, Milly (Online Submission, 2014)
The area of safety and accident prevention is of great concern to managers, because of the increasing number of deaths and accidents at work places. Using a case of Wakiso district, the study sought to investigate the relationship between collective commitment and management of health and safety in Ugandan secondary schools. The study employed a cross sectional survey design and collected data from 31 public and private secondary schools. The focus was on head teachers or deputies, teachers, wardens and school nurses. The correlation analysis indicated that there is a significant and positive relationship between collective commitment and managed health and safety (r= 0.567, p≤ 0.01). The study concluded that, ensuring health and safety in Ugandan secondary schools demands for collective involvement of stakeholders. It also requires a strict observation and enforcement of health and safety rules and regulations as well as the use of protection requirements.
Keywords: Safer schools; Health and safety; Collective commitment in schools; Secondary schools; Health in schools